Demographic Characteristics and Prescribing Patterns of Scleral Lens Fitters: The SCOPE Study. (September 2018) - Nau, Cherie B.; Harthan, Jennifer; Shorter, Ellen; Barr, Joseph; Nau, Amy; Chimato, Nicolette T.; Hodge, David O.; Schornack, Muriel M.
Abstract : Objectives: This study reports demographic characteristics of scleral lens providers and indications for scleral lens prescription as assessed by a worldwide online survey. Methods: The Scleral Lenses in Current Ophthalmic Practice: an Evaluation (SCOPE) study group designed the online survey regarding current scleral lens prescription and management practices. The Mayo Clinic Survey Research Center administered the survey, which was open from January 15 to March 31, 2015. Data from 989 responses were collated by the Survey Research Center and deidentified before analysis. Responses of individuals who had fit at least five patients with scleral lenses were analyzed in detail. Results: Most lens fitters were men (61%, n=800). Of survey respondents, 29% were 25 to 34 years; 22%, 35 to 44 years; 22%, 45 to 54 years; and 26%, more than 55 years (n=806). For 29% of all respondents, professional training was completed between 2009 and 2014 (n=804). Most (54%) fit their first patient between 2010 and 2015, with the earliest lens fit reported in 1956 (n=634). Most respondents (63%) worked primarily in private, group, or retail practice (n=811). Scleral lenses were most often prescribed for corneal irregularity (74%), followed by ocular surface disease (16%) and uncomplicated refractive error (10%) (n=673). Conclusions: Eye care providers of all ages are fitting scleral lenses. The number of individuals who fit this lens modality has increased during the past decade. Scleral lenses are being fit by providers in a wide range of practice settings. Most scleral lenses are prescribed for corneal irregularity. Abstract : Supplemental Digital Content is Available in the Text.